Investigation of the stress corrosion cracking behavior on T24 material under the operational conditions in the water wall. (April 2021) - Ullrich, C.; Tillmann, W.; Rademacher, H.-G.; Zielke, R.; Körner, P.
Abstract: The requirements for materials and their strength significantly increased with the new generation of coal fired power plants operating at steam temperatures of up to 620 °C. Therefore, new materials were introduced to fulfill the defined needs. During the commissioning process of the first plant many cracks occurred in welds of T24 material. The cracks showed clear characteristics of stress corrosion cracking (SCC). Not knowing the exact parameters that lead to cracking, experiments in high temperature water were carried out. Slow tensile tests in a controlled environment are extremely well suited to generate information about material's SCC sensitivity. In the present paper, the influence of the temperature, the oxygen concentration of water, the pre-treatment of the specimen and the heat treatment to the SCC are investigated. Furthermore critical limits for the cracking are defined where possible.